2006
DOI: 10.1177/0361198106198800101
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Traffic Flow Quality Experienced by Drivers

Abstract: Freeway operating conditions are typically evaluated on the basis of the level-of-service (LOS) concept, which is defined according to traffic density, a macroscopic traffic parameter. Although density may provide general estimates of current traffic conditions, it generally fails to communicate the variability in the quality of traffic flow experienced by individual drivers. This variability may be caused by factors that are not effectively captured by density, such as travel lane, vehicle position within a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…One study found that motorists did not perceive six-scales of delay (A-F), but instead thought in terms of three: ''good, '' ''marginal,'' and ''poor'' (Fang et al, 2003). Other studies conclude that motorist perception of the quality of an intersection is highly variable and influenced by trees, aesthetics of the surroundings, the size of other vehicles such as SUVs and pick-up trucks, pavement quality, and aggressive driving (Flannery et al, 2006;Ko et al, 2006;Lee et al, 2007;Pecheux et al, 2004).…”
Section: Los and Urban Spacementioning
confidence: 99%
“…One study found that motorists did not perceive six-scales of delay (A-F), but instead thought in terms of three: ''good, '' ''marginal,'' and ''poor'' (Fang et al, 2003). Other studies conclude that motorist perception of the quality of an intersection is highly variable and influenced by trees, aesthetics of the surroundings, the size of other vehicles such as SUVs and pick-up trucks, pavement quality, and aggressive driving (Flannery et al, 2006;Ko et al, 2006;Lee et al, 2007;Pecheux et al, 2004).…”
Section: Los and Urban Spacementioning
confidence: 99%